Stratification by Multidimensional Approach for Rational Treatment of Asymptomatic Carotid Stenosis (SMART-K Study): Study Protocol - YOSHIDA, Kazumichi (Neurol Med Chir (Tokyo), 2020)
With recent advances in medical treatments for carotid artery stenosis (CS), indications for carotid surgery should be more carefully considered for asymptomatic CS (ACS). Accurate stratification of ACS should be based on the risk of cerebral infarction, and subgroups of patients more likely to benefit from surgical treatment should be differentiated. Magnetic resonance imaging (MRI) offers a non-invasive, accurate modality for characterizing carotid plaque. Intraplaque hemorrhage (IPH) seems the most promising feature of vulnerable plaque detectable by MRI. Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is a type II membrane protein of the C-type lectin family with an extracellular domain that can be proteolytically cleaved and released as a soluble form (sLOX-1). This sLOX-1 plays a key role in the pathogenesis of atherosclerosis, and elevated sLOX-1 concentrations correlate with thin or ruptured fibrous caps in patients with acute coronary syndrome. This ongoing study aims to clarify the incidence of ischemic stroke in patients with ACS and IPH confirmed by MRI, and to assess whether sLOX-1 could provide a biomarker for risk of future ischemic events. The study population comprises patients with ACS (>60% area stenosis) associated with MRI-diagnosed IPH receiving follow-up under medical treatment. Primary endpoints comprise transient ischemic attack, stroke or amaurosis resulting from concerned CS. Secondary endpoints comprise any stroke or surgical treatment for progressive luminal stenosis. The target number of patients is 120 and the observational period is 36 months. The study results could help identify individuals with ACS who are refractory to medical therapy.